2004
DOI: 10.1002/mame.200300346
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration of Poly(ε‐caprolactone)‐g‐TiNbO5 Nanocomposites via in situ Metal Complex Initiated Intercalative Polymerization

Abstract: Summary: The preparation of poly(ε‐caprolactone)‐g‐TiNbO5 nanocomposites via in situ intercalative polymerization of ε‐caprolactone initiated by an aluminium complex is described. These nanocomposites were obtained in the presence of HTiNbO5 mineral pre‐treated by AlMe3, but non‐modified by tetraalkylammonium cations. These hybrid materials obtained have been characterized by Fourier transform infrared absorption spectroscopy, wide‐angle X‐ray scattering, scanning electron microscopy, and dynamic mechanical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…22 The mechanical properties of different nanocomposites based on PLA and a pure PLA sample prepared under similar conditions are summarized in Table I.…”
Section: Effect Of the Nanofiller On Tensile Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The mechanical properties of different nanocomposites based on PLA and a pure PLA sample prepared under similar conditions are summarized in Table I.…”
Section: Effect Of the Nanofiller On Tensile Propertiesmentioning
confidence: 99%
“…We have previously shown that significant layered nanofiller dispersion into several polymer matrices can be successfully accomplished using in situ polymerization method, [18][19][20][21][22] solution process, 23 or melt intercalation technique. 24,25 In this work, PLA layered silicate nanocomposites were prepared using a melt intercalation process.…”
Section: Introductionmentioning
confidence: 99%
“…In their work on elaboration of poly(ε-caprolactone)-g-TiNbO5 nanocomposites and the measure of tensile properties, Bruzaud et al (2004) state that in general, the Young's modulus, expressing the stiffness of a material at the start of a tensile test, has shown to be strongly improved when layered silicate nanofillers are homogeneously dispersed into the polymer matrix. The mechanical properties of neat PLA and PLA nanocomposites at various clay loadings (1, 3 and 5 wt.%) are summarized in Table 1.…”
Section: Tensile Measurementsmentioning
confidence: 99%
“…As far as the state of the art in this field is concerned, the characterization of organic‐inorganic hybrid materials has been addressed by using several characterization tools. The structure of the organic matrix, the mobility and the interface characterization have been successfully addressed by using multinuclear solid state NMR, Raman, and IR spectroscopies, providing also information on conformational features and composition 25, 42–58. A wide overview of other methods and approaches to the characterization of organic–inorganic hybrid materials is provided in the book of Kickelbick as well as in several other papers or dedicated textbooks 1–2, 7, 9, 11…”
Section: Organic–inorganic Hybrid Materialsmentioning
confidence: 99%
“…Valuable methods to investigate the structure on the medium‐range scale of these materials are the small‐angle scattering ones such as small‐angle x‐ray scattering (SAXS) and small‐angle neutron scattering (SANS), which exploit the difference in scattering length density between the organic part and the metallic atoms of the inorganic component 23b, 23g, 67–72…”
Section: Organic–inorganic Hybrid Materialsmentioning
confidence: 99%